Endolithic growth of two Lecidea lichens in granite from continental Antarctica detected by molecular and microscopy techniques - Ríos, Asunción de los; Sancho, Leopoldo G.; Grube, M.; Wierzchos, Jacek; Ascaso, Carmen (New Phytologist, 2005)
9 pages, 4 figures Through the combined use of molecular and microscopy techniques, the endolithiclichens Lecidea cancriformis and Lecidea sp. were identified, even in the absence offruiting bodies, and positioned under epilithic lichens. Cells of both algal and fungalsymbionts were observed in fissures and cracks of the lithic substrate with no clearheteromerous structure. At the ultrastructural level, the two lichens differed in termsof their algal–fungal relationships. Only one genotype of Trebouxia ITS sequence was identified from specimensof Lecidea sp., Umbilicaria aprina and Buellia frigida from the same zone,which could be mainly determined by low availability of alga in these extremeenvironments. These lichens showed features typical of both chasmoendolithic and euendolithicmicroorganisms. Signs of biogeophysical and biogeochemical action on thesubstrate were detected close to fungal cells. This action seemed to be mainlyconditioned by the local physico-chemical features of the substrate. Evidencefor the biomobilization of elements by these endolithic lichens was found. L. cancriformis was observed to accumulate substantial amounts of calcium-richbiominerals. The combined approach proposed is useful for mapping the distribution of endolithiclichens and analysing the processes that occur in their microscopic environment. Peer reviewed